Autoimmune Complications after Hematopoietic Stem Cell Transplantation in Children with Nonmalignant Disorders. (19th January 2014) - Khalil, Abdalla; Zaidman, Irena; Bergman, Reuven; Elhasid, Ronit; Ben-Arush, Myriam Weyl
Abstract : Background . Hematopoietic stem cell transplantation (HSCT) remains the only curative treatment for many nonmalignant disorders, such as autoimmune disorders, inborn metabolic disorders, hemoglobinopathies, and immunodeficiency disorders. Autoimmune complications (AICs) after HSCT, such as autoimmune cytopenias, autoimmune hepatitis, primary biliary cirrhosis, and autoimmune cutaneous manifestations, are still neither well defined nor characterized. Patients . Between 2000 and 2012, 92 patients (47 males, 45 females) were treated with HSCT in our hospital, 51 with congenital hemoglobinopathies, 19 with primary immunodeficiency disease, 10 with metabolic disorders, five with Fanconi anemia, three with aplastic anemia, and four with familial hemophagocytic lymphohistiocytosis. Results . Mean age at HSCT was 6.4 years (range, 0.2–32 years) and mean duration of followup after HSCT was 6.81 years (range, 1–11 years). Sixteen (17.4%) patients developed chronic GVHD and five (5.4%) showed sclerodermatous features. Five (5.4%) patients were diagnosed with scleroderma manifestations, six (6.5%) with vitiligo, six (6.5%) with autoimmune hemolytic anemia (AIHA), six (6.5%) with idiopathic thrombocytopenia, three (3.3%) with mild leucopenia, two (2.2%) with aplastic anemia, two (2.2%) (one boy, one girl) with autoimmune thyroid disease, and one (1.1%) with autoimmune hepatitis. Conclusions . It was concluded that AICs are clinically significant complications after HSCT that contribute to morbidity but not to mortality. AICs are more frequent after HSCT for metabolic disorders, and sclerodermatous GVHD is more significant in children who underwent allogeneic HSCT for hemoglobinopathies. The potential to identify risk factors for AICs could lead to less morbidity and mortality and to maintain the patient's quality of life.